2005
DOI: 10.1002/pola.20961
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of poly(2‐ethylhexyl methacrylate) copolymers containing pendant, self‐complementary multiple‐hydrogen‐bonding sites

Abstract: The synthesis and characterization of copolymers containing 2‐ethylhexyl methacrylate and a quadruple‐hydrogen‐bonding site, 2‐ureido‐4[1H]‐pyrimidone methacrylate (UPyMA), are described. An analogous dimeric hydrogen‐bond‐containing copolymer based on 2‐ethylhexyl methacrylate and methacrylic acid (PEHMA‐co‐MAA) was also synthesized for comparative purposes. The glass‐transition temperatures of the poly(2‐ethylhexyl methacrylate‐co‐2‐ureido‐4[1H]‐pyrimidone methacrylate) (PEHMA‐co‐UPyMA) series increased line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
65
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 53 publications
13
65
1
1
Order By: Relevance
“…n-Butyl acrylate was chosen as the primary monomer in the random copolymers due to its low T g , but it was expected that copolymerization with the UPy acrylate monomer might increase the overall T g of the polymer, either due to the presence of hydrogen bonds and slowing of the chain dynamics or simply due to the steric effects on the backbone. As shown in Figure 1, a linear increase in T g with increasing incorporation of UPy was observed, consistent with prior reports of UPy-functional random copolymers; 49,55 note, however, that even at high UPy loadings, the polymer T g is still below room temperature and at least 40°C below the lowest temperature for rheological measurements. Figure 2 shows the overall effects on rheological properties of the increase in mole fraction of UPy acrylate in random copolymers at constant molecular weight (irreversible changes in the rheological data began to occur at temperatures greater than 120°C so higher temperature data are not included in the master curves).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…n-Butyl acrylate was chosen as the primary monomer in the random copolymers due to its low T g , but it was expected that copolymerization with the UPy acrylate monomer might increase the overall T g of the polymer, either due to the presence of hydrogen bonds and slowing of the chain dynamics or simply due to the steric effects on the backbone. As shown in Figure 1, a linear increase in T g with increasing incorporation of UPy was observed, consistent with prior reports of UPy-functional random copolymers; 49,55 note, however, that even at high UPy loadings, the polymer T g is still below room temperature and at least 40°C below the lowest temperature for rheological measurements. Figure 2 shows the overall effects on rheological properties of the increase in mole fraction of UPy acrylate in random copolymers at constant molecular weight (irreversible changes in the rheological data began to occur at temperatures greater than 120°C so higher temperature data are not included in the master curves).…”
Section: Resultssupporting
confidence: 79%
“…14,38,49,50 Although the low solubility of the UPy methacrylate monomer limited its incorporation to 10 mol % or less, a higher degree of control over the bulk properties can be achieved via this route by varying any number of parameters including the concentration of UPy's in the chain, the total molecular weight, and the type of comonomer. In particular, it has been demonstrated that the melt viscosity and adhesive properties of random copolymers of n-butyl acrylate and UPy-methacrylate 14 together with the creep compliance of random copolymers of ethylhexyl methacrylate and UPy-methacrylate 49 can be widely varied by the concentration of UPy's along the backbone.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] UPy-based supramolecular polymeric materials prepared from telechelic polymers by functionalization with UPy synthons 18,25,27,38,39 are promising candidates for applications. The rheology of the melt state of such UPy-telechelic polymers is more complex 40,41 than for unidirectionally associated telechelic monomers or for the coordinatively cross-linked polymer networks described by Craig [42][43][44] and co-workers. Unusual rheological behavior was observed by Rowan 45 and co-workers when they examined poly(THF) functionalized with modified adenine and cytosine.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, it is thus important to understand the rheological response for a proper control of the material behaviour. The effect of UPy addition on the linear viscoelasticity of supramolecular polymers has previously been investigated [20,[63][64][65][66]. However, few studies exist where the rheological response is characterised for a systematic variation of supramolecular side-group density [41,66,67].…”
Section: Introductionmentioning
confidence: 99%